Marketing for hospitality and tourism - Kotler, Philip, 1931- (Prentice Hall, 1999)
This book provides a rich depth of practical examples and applications, showing the major decisions that hospitality and travel managers face in their efforts to balance the organization's objectives and resources against varying customer needs and opportunities in the global marketplace.